Epistimologi Dalam Pembelajaran Pendidikan Pancasila: Analisis Pemikiran Immanuel Kant - Mushlihah Ainur Rohmah (Jurnal Inovasi Pendidikan Madrasah Ibtidaiyah, 2024)
Pancasila education in Indonesia plays a crucial role in shaping students' character in schools, including at Madrasah Ibtidaiyah (MI) Tahfidzul Qur'an Raudlatul Falah. However, this education often faces various challenges that reduce its effectiveness. The epistemological approach, which emphasizes critical and systematic thinking, is expected to address these issues by helping students deeply understand Pancasila values.This study aims to analyze the implementation of the epistemological approach in Pancasila education at MI Tahfidzul Qur'an Raudlatul Falah using Immanuel Kant's thoughts as the theoretical foundation. This research employs a qualitative method with a case study approach. Data were collected through participant observation, interviews with teachers and students, and documentation analysis. Data analysis was conducted using the Miles and Huberman model. The study found that the epistemological approach was implemented through teaching methods that encourage critical and systematic thinking, assignments analyzing issues and phenomena, and a democratic classroom atmosphere. Positive impacts of this implementation include improved student understanding of Pancasila values, critical and reflective attitudes, and openness to various perspectives. However, challenges included limited time, learning resources, and teacher training. The findings of this study can serve as a reference for other educational institutions in implementing the epistemological approach to enhance the quality of Pancasila education. Additionally, this study highlights the importance of teacher training and the provision of learning resources that support this approach.